PENGEMBANGAN BUKU SAKU PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT DI SMK NEGERI 1 LOGAS TANAH DARAT - Amanda Nopita; Dwi Putri Musdansi; Edi Kurniawan (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
This research aims to determine and the feasibility of developing a pocket book on electrolyte and non-electrolyte solution materials in State High School 1 Logas Tanah Darat. This research using research and development method with and development (R&D) with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. Data collection instruments used are through media expert validation sheets, material expert validation sheet, linguits expert validation sheet and a student response validation sheet. The data analysis technique used which is calculating the validation assessment percentage score. The results showed that the interactive learning media a pocket book that was developed fulfilled the valid categories of by media expert of 89,44%, materiall experts of 88,88%, and linguist expert of 89,28%. This learning media also fulfills a valid category which students can use with persentage of 90,56%